Eating habits, smoking and toothbrushing in relation to dental caries: a 3-year study in Swedish female teenagers - K. BRUNO-AMBROSIUS, G. SWANHOLM, & S. TWETMAN (Paediatric Dentistry, 2005)
The ‘classic’ relationship between diet and dental caries has been reviewed in recent years, and the relative importance of sugar consumption in caries aetiology is now seen as a modifying risk factor rather than a primary causative factor [1,2].